2010
DOI: 10.1088/0256-307x/27/10/106202
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of Micro Crack for Brittle Fracture in Magnetic Field

Abstract: The influence of magnetic field on the nucleation of micro crack for brittle fracture is studied. The dynamic equation of micro crack in magnetic field is deducted. Using the crack model of a single pile-up group of dislocation, the growth speed of micro crack at a low growth speed stage is derived. To understand the effect of the magnetic field on the nucleation, the mean nucleation rate of micro crack in magnetic field is obtained. The derived result on the mean nucleation rate of micro crack shows that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The interfacial tractions in the front of the interface and behind the tip of a crack lying on the interface between two dissimilar, linearelastic, anisotropic materials (see Fig. 5) are given by [10,35]…”
Section: Stress Intensity Factors Of An Interface Crack With Frictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interfacial tractions in the front of the interface and behind the tip of a crack lying on the interface between two dissimilar, linearelastic, anisotropic materials (see Fig. 5) are given by [10,35]…”
Section: Stress Intensity Factors Of An Interface Crack With Frictionmentioning
confidence: 99%
“…[5][6][7][8] Therefore, it is necessary to develop an accurate analytic method of solving the bimaterial interface crack problem, which could make a contribution to the interface failure studies of the TBC. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] [4] Williams [12] performed an asymptotic analysis of the elastic fields at the tip of an open interface crack, and found that the stresses are of an oscillatory manner and the upper and lower surfaces of the crack should wrinkle and overlap near the ends of the crack, when the crack surfaces are assumed to be traction-free. Erdogan [13] and England [14] proposed the same analytical solutions.…”
Section: Introductionmentioning
confidence: 99%